Unthinking modernity : Innis, McLuhan, and the Frankfurt School - Stamps, Judith, 1946- (McGill-Queen's University Press, 1995)
"Harold Innis and Marshall McLuhan have received much recognition as communications theorists, but Judith Stamps argues that the scope and value of their work extends far beyond this. She demonstrates that Innis and McLuhan used their studies of media to develop a critique of Western thought and culture and that their insights, derived from the North American experience, added a new, media-based perspective to such a theory." "Using a combination of historical and textual analysis, Stamps shows that Innis and McLuhan were dialecticians who developed an alternative route to a critique of reason through a media-based study of the limits of the positivist traditions that still inform much of Western thought. She demonstrates that Innis and McLuhan created variations of the "negative dialectics" proposed by members of the Frankfurt school, specifically Theodor Adorno and Walter Benjamin. In doing so Innis and McLuhan invented a uniquely Canadian version of critical theory, a fusion of critical political economy and critical rationality associated with the early Frankfurt school." "Unthinking Modernity raises issues about how modernity can best be understood and offers unique perspectives on how economics, politics, and media intertwine to create personal and social consciousness."--Jacket